The Practice of Using Specialized Knowledge to Counteract Dissemination of Extremist Materials - Oleg Yu. Antonov (Теория и практика судебной экспертизы, 2021)
The paper describes the directions of counteracting extremist materials dissemination in Russia and their results as seen in the Federal List of Extremist Materials of the Ministry of Justice of the Russian Federation, statistics of the State Information and Analytical Agency of the Ministry of Internal Affairs of Russia on the number of registered crimes and persons brought to criminal responsibility as well as the Judicial Department at the Supreme Court of the Russian Federation on the state of criminal record and activities of the federal courts of general jurisdiction and justices of the peace.The study aims to develop recommendations to optimize the judicial and investigative use of specialized knowledge to counteract the dissemination of extremist materials. The research tasks are: examining the shortcomings of preliminary investigation, analyzing the current judicial practice of administrative proceedings, and formulating proposals for the best use of specialized knowledge to identify the signs of hatred and enmity in the disseminated products. The study reveals the problems of the investigative practice related to the definition of the forensic examination subject for various categories of objects in terms of their material carriers. The author also notes cases of unjustified expansion of the subject of expert examination of extremist materials. Furthermore, the article identifies the shortcomings and positive experience in judicial practice on publicly available administrative cases on recognition materials as extremist and prosecution persons for inciting hatred or hostility or for posting on the Internet materials included in the Federal List of Extremist Materials. Finally, forensic recommendations on using specialized knowledge in the analysis of disseminated extremist materials are offered.